2020
DOI: 10.3847/1538-3881/abb806
|View full text |Cite
|
Sign up to set email alerts
|

ACCESS: Confirmation of No Potassium in the Atmosphere of WASP-31b

Abstract: We present a new optical (400–950 nm) transmission spectrum of the hot Jupiter WASP-31b (M = 0.48 M J; R = 1.54 R J; P = 3.41 days), obtained by combining four transit observations. These transits were observed with IMACS on the Magellan Baade Telescope at Las Campanas Observatory as part of the ACCESS project. We investigate the presence of clouds/hazes in the upper atmosphere of this planet, as well as the contribution of stellar activity on the observed features. In addit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…Evidence for a grey cloud deck was also obtained by Barstow et al (2017), whereas other comparative studies found some weak H 2 O (Pinhas et al 2019;Welbanks et al 2019) and NH 3 features (MacDonald & Madhusudhan 2017;Min et al 2020). The existence of the K signature has been called into question by recent observations using the FOcal Reducer and low dispersion Spectrograph 2 (FORS2) and the Ultraviolet and Visual Echelle Spectrograph (UVES) on the Very Large Telescope (VLT; Gibson et al 2017Gibson et al , 2019 and the Inamori-Magellan Areal Camera and Spectrograph (IMACS) on the Magellan Baade Telescope (McGruder et al 2020).…”
Section: R P (R J )mentioning
confidence: 95%
“…Evidence for a grey cloud deck was also obtained by Barstow et al (2017), whereas other comparative studies found some weak H 2 O (Pinhas et al 2019;Welbanks et al 2019) and NH 3 features (MacDonald & Madhusudhan 2017;Min et al 2020). The existence of the K signature has been called into question by recent observations using the FOcal Reducer and low dispersion Spectrograph 2 (FORS2) and the Ultraviolet and Visual Echelle Spectrograph (UVES) on the Very Large Telescope (VLT; Gibson et al 2017Gibson et al , 2019 and the Inamori-Magellan Areal Camera and Spectrograph (IMACS) on the Magellan Baade Telescope (McGruder et al 2020).…”
Section: R P (R J )mentioning
confidence: 95%
“…In particular, as several groups of gasses are associated with clouds that condense at similar temperatures on hot Jupiters (e.g., TiO/VO, aluminum, and calcium at the highest temperatures, iron, magnesium, silicon, chromium, and manganese at moderate temperatures, and potassium and sodium at lower temperatures, see Figure 1), measuring the absolute abundances of these gases and their ratios as a function of planetary temperature and gravity could help constrain the condensation sequence in exoplanet atmospheres (Lothringer et al, 2020). However, while many species have been detected for ultra-hot Jupiters (e.g., Ben-Yami et al, 2020;Cabot et al, 2020;Fossati et al, 2010;Haswell et al, 2012;Hoeijmakers et al, 2018;Nugroho et al, 2020;Sing et al, 2019;von Essen et al, 2019;Yan et al, 2019), suggesting largely cloud-free atmospheres, efforts at lower temperatures have yielded mixed results due to controversial detections that are difficult to replicate (e.g., Chen et al, 2018;Cubillos et al, 2020;Espinoza et al, 2019;Gibson et al, 2019Gibson et al, , 2017McGruder et al, 2020;Sedaghati et al, 2017;Seidel et al, 2020;Sing et al, 2015;Vidal-Madjar et al, 2013) and aerosol opacity at optical wavelengths that reduce the amplitudes of atomic and molecular absorption features (Charbonneau et al, 2002;Heng, 2016;Pont et al, 2008;Sing et al, 2016).…”
Section: Future Observationsmentioning
confidence: 99%
“…Most planets in this sample were found to have some level of cloudiness and/or haziness, with WASP-17b showing evidence of K (Sedaghati et al 2016) and Na (Wood et al 2011;Zhou & Bayliss 2012;Sing et al 2016) absorption. Signs of K absorption were initially detected for WASP-31b as well (Sing et al 2015), but later ground-based observations at lowand high-resolution confidently disproved this space-based result, finding no trace of the alkali metal in the atmosphere of this planet (Gibson et al 2017(Gibson et al , 2019McGruder et al 2020). Furthermore, a slope in the visible region due to scattering in the atmosphere can also be found in HAT-P-32Ab (Mallonn & Strassmeier 2016;Alam et al 2020) and WASP-31b (McGruder et al 2020).…”
Section: Wasp-88b In Contextmentioning
confidence: 97%
“…This should come as no surprise, however, as there is now mounting evidence that clouds can be common even at higher equilibrium temperatures (e.g. Wakeford et al 2017;Espinoza et al 2019;Alam et al 2020;Yan et al 2020;McGruder et al 2020).…”
Section: Wasp-88b In Contextmentioning
confidence: 99%